Nutrisi Seimbang Untuk Premenopause: Efek Penyuluhan Gizi Terhadap Sikap Konsumsi Ibu - Fadiya Asminah; Luh Putu Widiastini; Ni Putu Mirah Yunita Udayani (STIKES Bina Usada Bali, 2026)
Background: Poor nutrition is a risk factor for various non-communicable diseases. Limited knowledge and negative attitudes toward balanced nutrition can influence dietary consumption patterns. Objective: To determine the effect of balanced nutrition education on the attitudes of premenopausal women toward balanced nutrition. Methods: This study employed a pre-experimental design with a One Group Pretest–Posttest Design involving 32 premenopausal women. The intervention consisted of education on balanced nutrition, and attitudes were measured using a questionnaire administered before and after the education. Data were analyzed using the Wilcoxon signed-rank test. Results: The average attitude score before the education was 60.51 (SD 9.307), increasing to 70.50 (SD 7.713) after the education. A p-value of 0.000 (<0.05) indicated a significant difference. Conclusion: Balanced nutrition education significantly improved the attitudes of premenopausal women toward consuming balanced nutrition. These findings may serve as a consideration in providing comprehensive midwifery care for premenopausal women